Growth and production response of mung bean (Vigna radiata L) by application of mycorriza and Penicillium sp in paddy lands - Nursiani, Lubis; Abdul, Rauf; T., Sabrina (Talenta Publisher, 2020)
ABSTRACT This study aimed to evaluate the effect of mycorrhiza and Penicilliumsp on the growth and production of mung beans in paddy land. The design of this experimental research was a factorial Randomized Block Design (RBD) with 2 factors and 3 replications. The first factor was the dosage of mycorrhiza consisting of 0 g/plant; 5 g/plant; 10 g/plant; and 15g/plant. The second factor was the type of phosphate solubilizing microbes consisting of withoutPenicilliumsp; Penicilliumspfrom Mursala island (20 ml/plant); Penicilliumsp collection taken from soil biology laboratory of faculty of agriculture USU (20 ml/plant). The results showed that the dosage of Mycorrhiza and Penicilliumsp were not significantly affected the height of mung bean plants, however, it significantly affected the population of Penicillium sp. The application of 15 g Mycorrhiza with Penicilliumsp from Mursala was the best treatment for the growth of mungbean plants at 4 weeks after planting (42.98 cm) and the interaction of Mycorrhiza15 g/plant and PenicilliumspMursala produced the best seeds/plant of 16.76 g/plant. REFERENCES Adiningsih, S. 2004. Nutrient dynamics in soil and nutrient uptake mechanisms. Soil Research Center. Ministry of Agriculture. Jakarta. Badan Pusat Statistik. 2016. Production of Cassava and Green Beans by Province in 1993-2015. Jakarta. Budiman, A. 2004. Application of Cashing and Arbuscular Mycorrhizal Fungi on Ultisols and the Effects on the Development of Soil Microorganisms and the Result of Semi Corn (Zea mays L.). Thesis of the Faculty of Agriculture. Andalas University. Padang. De datta, S.K. 1990. Principle and Practice of Rice Production. New York. Dobermann, A. and T. Fairhurst. 2000. Rice, Nutrient disorders and nutrient management. IRRI and Potash and PPI/PPIC. Manila, Philipina. Fitriatin, B. M., A. Yuniarti., O. Mulyani., F. S. Fauziah., dan M. D. Tiara. 2009. Effect of Microbial Solvents on Phosphate and Fertilizer P on Available P, Phosphatase Activity, P on Plants and Upland Rice Results on Ultisol. Agriculture Journal20 (3) : 210 – 215. Harahap, F.S. 2009. Pengujian pengolahan tanah konservasi dan inokulasi mikoriza terhadap sifat fisik dan kimia tanah serta produksi beberapa varietas kacang tanah (Arachis hypogaea. L) Universitas Sumatra Utara Medan. Skripsi. Hasanuddin and Bambang. G. M. 2004. Utilization of phosphate and mycorrhizal microbial solvents to repair available phosphorus, soil phosphorus uptake (ultisol) and maize yields (on ultisol). Journal of agricultural sciences Indonesia, 6 (1): 8 – 13. Husin, E.F. 2000. Fungus Arbuskula Mycorrhiza. Andalas University Faculty of Agriculture. Padang. Illmer, P. and F. Schinner. 1992. Solubilization of inorganic phosphate by microorganisms isolated from forest soils. Journal Soil Biology Biochem, 24 (4): 389 – 395. Sastrahidayat, R. 2011. Science of fungi (Mycology). Universitas Brawijaya Press. Malang. Sembiring and Fauzi. 2017. Bacterial and Fungi Phosphate Solubilization Effect to Increase Nutrient Uptake and Potatoes (Solanum tuberosum L.) Production on Andisol Sinabung Area. Journal of Agronomy 16 (3) : 131 – 137. Sitrianingsih. 2010. The Effect of Arbuscular Vesicular Mycorrhiza Inoculation on the Growth of Pandak Pule Seedlings (Rauvolfia verticillata Lour.) Publication Text. Biology Department Faculty of Mathematics and Natural Sciences Sebelas Maret University Surakarta. Suratmin, D. Wakano, D. Badwi. 2017. The use of compost and phosphorus fertilizer on the growth of green bean plants. Journal of Biology Science & Education, 6 (2): 148 – 158. Susanti, R., Afriani, A., Harahap, F.S., Fadhillah, W., Oesman, R. and Walida, H., 2019. Application Micoriza and Baean Varieties by Conservation Tillage for Biological Soil Properties Improvement. Jurnal Pertanian Tropik, 6 : 34-42. Syawal, F., Rauf, A. dan Rahmawaty. 2017. Upaya rehabilitasi tanah sawah terdegradasi dengan menggunakan kompos sampah kota di Desa Serdang Kecamatan Beringin Kabupaten Deli Serdang. Jurnal Pertanian Tropik 4 3 :183-189. Syawal, F., Rauf, A., Rahmawaty, R. dan Hidayat, B. 2017. Pengaruh Pemberian Kompos Sampah Kota Pada Tanah Terdegrdasi Terhadap Produktivitas Tanaman Padi Sawah Di Desa Serdang Kecamatan Beringin Kabupaten Deli Serdang. Dalam Prosiding SEMDI-UNAYA (Seminar Nasional Multi Disiplin Ilmu UNAYA) (Vol. 1, No. 1, pp. 41-51). Wakelin, S.A, V.V.S.R. Gupta, P.R Harvey, and M.H. Ryder. 2007. Commonwealth Scientific and Industrial Organisation (CSIRO) Land and Water, PMB 2, Glend Osmon, SA 5064, Australia. Whitelaw. 2000. Growth promotion of plants inoculated with phosphate solubilizing fungi. Journal Adv. Agron 69 : 99 – 151.